“Plan de negocios para la creación de una microempresa de papas chinas procesadas de forma artesanal” - Ortega Acosta, Celena Mireya (2024)
This research aims to develop an entrepreneurship project for the creation of a company dedicated to the production and commercialization of Papa China snacks in Latacunga – Cotopaxi, Ecuador. To carry out this work, the first step was identify the diagnosis of the problem through a critical analysis; the theoretical foundation was supported by bibliographic sources, and surveys were used as techniques and instruments to gather essential information contributing to the determination and justification of the research problem. The approach used for the development of this project was quantitative-descriptive, focusing on relevant analyses such as financial study by examining the amounts involved in the economic activities of the company, such as the initial investment, cost budget, among others. The proposed solution to achieve the result as soon as project's execution was carried out through a market study, revealing that 98.5% of the population would be willing to purchase the Papa China snack. The initial investment is $46,369.57, with 50% covered by a bank loan and 50% through self-financing. Through economic and financial analysis, a positive Net Present Value (NPV) of $26,672.02 was obtained, and the Internal Rate of Return (IRR) was favorable at 46%. Additionally, the cost-benefit ratio was 1.14, indicating that for every dollar invested, the company earns 14 cents. This planning process suggests that the business idea is feasible and profitable.